Effect of ZnO addition on the structure, microstructure and dielectric and piezoelectric properties of K0.5Na0.5NbO3 ceramics - Leandro Alfredo Ramajo; Jonathan Taub; Miriam Susana Castro (Materials Research, 2014)
Microstructure, structure and electrical and dielectric properties of ZnO-doped K0.5Na0.5NbO3 (KNN) ceramics were investigated. Powders were obtained by the conventional solid-state method. Samples doped with 0 to 1 mol% of ZnO were sintered at 1125 °C for 2 h. Through XRD spectra, the perovskite structure was detected, in addition to small peaks corresponding to secondary phases. It was also observed that zinc changed the microstructure and grain size of KNN ceramics. The addition of 0.5 mol% of Zn2+ produced a softening effect in the ferroelectric properties of the material, and increased its final density. Conversely, the addition of 1 mol% of Zn2+ reduced the sample densification.